2019
DOI: 10.1177/0038026119878097
|View full text |Cite
|
Sign up to set email alerts
|

Decolonising and re-theorising the meaning of democracy: A South African perspective

Abstract: Historically and today, social movements have often been at the forefront of envisioning the content of democracy. Although democracy itself is a contested concept, in general, definitions and measures of democracy are often drawn from the canon and experiences of the global North. Contributing to the growing decolonisation movement in the social sciences, this article examines understandings of democracy in the context of post-apartheid South Africa. It considers how ordinary people conceptualise democracy th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…There are, no doubt, other alternatives. From a decolonial perspective the point is not to develop a new 'universal' definition but rather to encourage a pluriversality of views (Brooks et al, 2020) that by their very circulation create other possible knowledges and ways of knowing. What a decolonizing perspective on dominant international anti-corruption knowledge offers then, is a way of contesting the universalism inherent in this knowledge, by showing how and why all knowledge is situated and the product of particular times and places.…”
Section: Discussionmentioning
confidence: 99%
“…There are, no doubt, other alternatives. From a decolonial perspective the point is not to develop a new 'universal' definition but rather to encourage a pluriversality of views (Brooks et al, 2020) that by their very circulation create other possible knowledges and ways of knowing. What a decolonizing perspective on dominant international anti-corruption knowledge offers then, is a way of contesting the universalism inherent in this knowledge, by showing how and why all knowledge is situated and the product of particular times and places.…”
Section: Discussionmentioning
confidence: 99%
“…A good starting point is clarifying that the concept and task of decolonization is open to wide interpretation. For example, as Brooks et al (2020) note, on one end of the spectrum, there are those who advocate the production of indigenous knowledge systems that are distinct from the colonizer's influence; others advocate an approach that identifies the "coloniality of knowledge" (Quijano, 2000(Quijano, , 2007 and de-centers normative understandings of modernity and Eurocentrism as reflected in values such as civilization, development, and democracy (Dunford, 2017).…”
Section: A Decolonial Reading Of the Coloniality Of Democracymentioning
confidence: 99%
“…Gordon, 2010)-an issue that for a long time has been considered a contradiction in terms among democratic theorists (Mann, 2005). Yet, growing discussions about this relationship in recent years (e.g., see Brooks et al, 2020;Güven, 2015;Singh, 2018) have raised provocative questions that approach democracy "cautiously, curiously, even skeptically, asking whether the constituent features and conceits of European modernity have ever permitted us to understand or practice it" (Brown, 2010a: n.p). In particular, Güven (2015) has gone as far as suggesting that "The discourse of democracy is the continuation of a (neo)colonial world order" (xi) in which colonization is employed as a strategy by democracies (and other regimes, of course) for geopolitical and economic purposes-namely, land and resources appropriation, dispossession and enslavement.…”
Section: Introductionmentioning
confidence: 99%
“…Their ability to voice through trade unions has only been achieved following a prolonged period of struggle. Indeed, research into the related concept of democracy in isiZulu has found that it has been understood as an ‘ongoing struggle for a better life’ (Brooks et al., 2020, p. 24).…”
Section: Conceptualising Voice In the Majority World: South Africa An...mentioning
confidence: 99%